Deficits in emotional cognition among individuals with conduct disorder: theoretical perspectives - Li, Xue; Kou, Hui; Bi, Taiyong; Peng, Zuoyang (Frontiers in Psychiatry, 2024)
Conduct disorder refers to a persistent and repetitive pattern of problematic behavior, and is usually accompanied by deficits in cognitive processing of emotional stimuli. Behavioral and physiological correlates of these deficits have been the subject of sufficiently many investigations. Meanwhile, several theories concerning conduct disorder have been developed. However, the validity of these theories to explain the emotional processing deficits among conduct-disordered individuals has not been tested. Here we summarized four relevant theories, including “social-cognitive theory and social-information-processing theory”, “violence inhibition model”, “optimal stimulation/arousal theory and stimulation/sensation seeking theory”, and “fearlessness theory”, and discussed their validity in predicting the emotional processing deficits among conduct disordered individuals. Future directions on the theories and evidence were proposed.